Training for farmers on cattle and pig breeding practices in Mai Sơn, Sơn La - Thanh, Lo Quang; Thinh, Nguyen Thi; Thuong, Le Thi; Hai, Lo Van; Tien, Ngo Quang; Ngan, Nguyen Thi (International Livestock Research Institute, 2024)
Sơn La province is also focused on livestock development and has established plans to improve livestock breeds in line with market demands. According to Plan No. 295/KH-UBND, issued by the People's Committee of Sơn La Province on December 13, 2023, regarding the implementation of large livestock development in difficult and zone III communes for 2024 and the following years in Sơn La province, there is an emphasis on promoting the application of advanced technology in the selection, breeding, and production of high-quality cattle breeds suitable to the province's natural conditions, replacing underperforming breeds. The plan also focuses on developing native specialty breeds, crossbreeds, and high-value imported breeds that ensure food safety, environmental sustainability, and biosecurity. Thus, training on breeding and livestock practice for local officials and farmers is essential.